Malaysian Financial Reporting Standard 139 financial instruments : recognition and measurement adoption and intellectual capital performance : evidence from the Malaysian financial sector - Abdullah Jihad Rasmi Rabaya,; Noradiva Hamzah,; Norman Mohd Saleh, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The transition from tangible asset to intangible asset in the knowledge-based economy has brought several changes in terms of value creation. The value creation generated from company’s intellectual capital has a major impact on company value and performance. The performance of intellectual capital in value creation (generating company’s capabilities which in turn increased the company’s performance) could assist investors and company’s management to visualize the importance of intangible assets. MFRS 139 adoption facilitates the management and investors by providing better information environment that could enhance company’s intellectual capital performance, especially the financial institution’s holding companies. MFRS increases the quality of financial information, transparency level and enhances the business information environment that could in turn improves company performance. Giving attention to knowledge management theory, this study examines the association between MFRS 139 adoption and intellectual capital performance and its components. This study uses secondary data obtained from Data-stream database and annual reports of Malaysian financial institution holding companies that are listed in the main market in Bursa Malaysia from 2005 to 2015. The empirical result indicates that the MFRS 139 adoption has a significantly positive effect on company’s intellectual capital performance.